2020
DOI: 10.1101/2020.09.11.20192989
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning for Integrating Social Determinants in Cardiovascular Disease Prediction Models: A Systematic Review

Abstract: Background: Cardiovascular disease (CVD) is the number one cause of death worldwide, and CVD burden is increasing in low-resource settings and for lower socioeconomic groups worldwide. Machine learning (ML) algorithms are rapidly being developed and incorporated into clinical practice for CVD prediction and treatment decisions. Significant opportunities for reducing death and disability from cardiovascular disease worldwide lie with addressing the social determinants of cardiovascular outcomes. We sought to re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Machine learning has so far played a role in identification in a broad range of studies from learning biological mechanisms 26 to establishing the multivariate empirical relationship between the probability of disease outbreak and environmental conditions 27 . Given the complex relationships and possible mediations between multi-level factors 28 , by leveraging new data sources there is the opportunity to use and develop machine learning methods for the interpretable identification and assessment of the source and magnitude of a wide variety of multi-level factors in health outcomes. • Design of interventions.…”
Section: • Identification Of Factors and Their Relation To Health Outcomesmentioning
confidence: 99%
“…Machine learning has so far played a role in identification in a broad range of studies from learning biological mechanisms 26 to establishing the multivariate empirical relationship between the probability of disease outbreak and environmental conditions 27 . Given the complex relationships and possible mediations between multi-level factors 28 , by leveraging new data sources there is the opportunity to use and develop machine learning methods for the interpretable identification and assessment of the source and magnitude of a wide variety of multi-level factors in health outcomes. • Design of interventions.…”
Section: • Identification Of Factors and Their Relation To Health Outcomesmentioning
confidence: 99%
“…Beyond work capturing social determinants using machine learning from person-generated sources [1,48], a recent systematic review analyzed how social determinants have been used to study the risk factors of cardiovascular diseases [63]. While common social determinants like age, gender, race, income, and education have been analyzed for estimating cardiovascular risk, most commonly the factors considered are at the individual-level even though research has clearly shown that community-level factors such as a person's neighborhood's overall income can also affect their disease risk.…”
Section: Integrating Social Determinants Of Health In Machine Learnin...mentioning
confidence: 99%
“…While common social determinants like age, gender, race, income, and education have been analyzed for estimating cardiovascular risk, most commonly the factors considered are at the individual-level even though research has clearly shown that community-level factors such as a person's neighborhood's overall income can also affect their disease risk. [63]. Moreover, most studies to-date using machine learning models have involved associative studies.…”
Section: Integrating Social Determinants Of Health In Machine Learnin...mentioning
confidence: 99%
“…With the advancement of technology, the treatment of coronary heart disease has recently been mentioned in numerous studies that have gotten tremendous attention within the healthcare industry. This can be proven by researchers from New York University's School of Global Public Health and Tandon School of Engineering, screened more than 1,600 articles and focused on 48 peer-reviewed studies published in journals between 1995 and 2020 [2]. They found that applying machine learning models improved the ability to predict cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 98%